Elimination of arsenic-containing emissions from gasification of chromated copper arsenate wood. (1st October 2016) - Kramb, Jason; Konttinen, Jukka; Backman, Rainer; Salo, Kari; Roberts, Michael
Highlights: Bench-scale gasification tests of CCA wood. Product gas cleaning system for removing arsenic using a hot filter. Equilibrium modeling of arsenic behavior using combined thermodynamic database. Abstract: The behavior of arsenic in chromated copper arsenate containing wood during gasification was modeled using thermodynamic equilibrium calculations. The results of the model were validated using bench-scale gasification tests. It is shown that over 99.6% of arsenic can be removed from the product gas by a hot filter when the gas is cooled below the predicted condensation temperature.